2022
DOI: 10.1108/jkm-07-2021-0584
|View full text |Cite
|
Sign up to set email alerts
|

Impacts, lessons learnt and envisioning the future of firms under COVID-19 – implications for knowledge management

Abstract: Purpose The purpose of this study is to examine the significance of knowledge management as a tool for firms to adapt to an ongoing unprecedented crisis. Moreover, in considering the knowledge-based view of the firm, the study will ascertain the impacts, lessons learnt and how firms envisage their future under the current unpredictable regime from the viewpoints of firm owners/managers. Design/methodology/approach A qualitative data collection approach was selected, with face-to-face and online interviews un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…KM is paramount for organizational survival and effectiveness in turbulent, rapidly changing environments (Yates and Paquette, 2011). The scientific managerial literature focusing on KM in times of pandemics has over the years been widely ignored (Ammirato et al, 2020;Ng et al, 2022). Specifically, empirical research of KM in the context of COVID-19 is still under development (Ammirato et al, 2020).…”
Section: Organizational Km During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…KM is paramount for organizational survival and effectiveness in turbulent, rapidly changing environments (Yates and Paquette, 2011). The scientific managerial literature focusing on KM in times of pandemics has over the years been widely ignored (Ammirato et al, 2020;Ng et al, 2022). Specifically, empirical research of KM in the context of COVID-19 is still under development (Ammirato et al, 2020).…”
Section: Organizational Km During the Covid-19 Pandemicmentioning
confidence: 99%
“…Knowledge management (KM) refers to obtaining the correct knowledge at the appropriate time and place (Oktari et al, 2020). As an invaluable strategic organizational tool, KM can enhance agility and effectiveness (Ng et al, 2022). "KM practices, such as knowledge creation, knowledge dissemination, knowledge storage and knowledge…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 crisis has posed new challenges for businesses and their management, pushing them to instil a deeper sense of cohesion and solidarity amongst the organisational members (Ng et al , 2022). Generally, strongly committed employees are more inclined to devote their efforts and resources towards attaining the organisation's goals (Klein et al , 2012); thus, improved performance is anticipated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of business, most organisations have encountered crises because of new operational challenges thrown by COVID-19. In dealing with disruptive events during such a crisis, studies have shown that effective and efficient knowledge management can support business organisations and help them make appropriate decisions to mitigate potential damages (Ammirato et al , 2020; Ng et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As far as business organizations are concerned, the massive impact of the pandemic has also affected Chinese companies. Many companies suffered a huge existential crisis during the pandemic (Wang et al, 2020;Ng et al, 2022). Meanwhile, people have been forced to adopt a series of measures July 2022 | Volume 13 | Article 882029 Health Belief on Knowledge Sharing to avoid infection, such as wearing masks, keeping social distance, or even working from home, which have adversely affected their work and life (Li et al, 2021a;Aldianto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%